Proof of concept studies in mental health systems research: strategy and steps - Luis Salvador-Carulla; Hossein Tabatabaei-Jafari; Cindy Woods; Sue Lukersmith (International Journal of Mental Health Systems)
Abstract Background The implementation of interventions, digital tools, and policy plans in health systems research is highly complex. Proof-of-Concept (PoC) studies facilitate the development of these applications although they are rarely conducted or reported in mental health research. This paper describes the principles and processes to conduct PoC studies in mental health systems research. Method The Technology Readiness Level in Implementation Sciences (TRL-IS) serves as the reference framework for this study. A ‘lessons learned’ process was applied to refine the concepts and develop a research strategy based on previous experiences with PoC studies. This process incorporated insights gained from a scoping review, case studies and discussion with both a core group and an extended group of experts. Results PoC studies assess the workability of an application, formulating the basic concept and determining whether its functionality can be transformed into a real prototype to be tested as intended via a pilot study and later demonstrated in the real world. The strategy to conduct PoC studies should be part of the analysis of readiness of any application in health system’s research. The first four levels of readiness in the TRL-IS scale include (1) foundational knowledge, (2) formalised prior knowledge base, (3) completion of a workable PoC, and (4) prototyping. It’s design requires input from experts in all four levels. Twenty-three main elements relevant to PoC have been identified in these four phases. Discussion PoC is generally omitted (or not reported) in mental health systems research. Researchers should be actively encouraged to overcome this omission. A common language, classification and vocabulary is needed for implementation science which incorporate this domain. The description of the specific activities conducive to PoC and prototyping should be provided. Training on the use of the TRL-IS framework including expert knowledge should also be promoted in mental health system research.